Trevor Dollar Estate Android Application - Bete, Grace (Midlands State University, 2020)
Trevor Dollar Real Estate Android Application is a mobile based software that helps people to sell or rent properties. The android application has a searching facility where people can search for a specific property utilizing different particulars, for example, that of value, location and so forth. Moreover the android application will send notifications of when a payment is expected and when there is another posting inside the firm. Aside from that the android application additionally calculates the interest to be charged for a given property. The android application will be gotten to by means of Wi-Fi or using mobile data of any mobile network operator on any gadget that has an android working framework running on it.